Filosofi Membelah Anak Panah: Memahami Kehidupan - Saragi, Oliver Richardo; Muhammad Fikriansah; Hasugian, Lewi Ebenezer (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to present a critical review of the book titled "Membelah Anak Panah" by Prem Rawat. The research method used in this study is qualitative descriptive to analyze the content of the book. The study results indicate that the book enlightens inner strength, offering practical advice on life, success, and relationships. It presents touching stories and unique illustrations that invite attention to the simple realities about oneself, living life, and the present moment. The book "Membelah Anak Panah: Understanding Life" urges us to be aware of life, containing many motivational words, life illustrations, wisdom, and problem-solving questions and answers about life issues.